A Matter of Vertical Position: Consequences of Ostracism Differ for Those Above Versus Below Its Perpetrators. (March 2014) - Schoel, Christiane; Eck, Jennifer; Greifeneder, Rainer
Vertical position in space has been linked to perceptions of power, and high-power individuals have been shown to be less influenced by both the situational context and other people. Building on this literature, we hypothesized that a high spatial position as compared with a low one would reduce the threat from social exclusion and might help prevent aggressive acts of retaliation. To investigate this hypothesis, two arrangements of "Cyberball"—a classic manipulation of social exclusion—were compared: In the standard arrangement, participants are positioned below the excluding players; for the new arrangement, the standard arrangement was vertically flipped, so that participants were positioned above the excluding players, and thus "aloof" from the situation. Results show that only individuals positioned below (implying low power), but not individuals positioned above (implying high power), exhibited increased aggression when being ostracized. Threatened need for control and negative mood mediated the tendency toward aggressive behavior.